CORRELATION BETWEEN CRANIAL BASE ANGLE AND VARIOUS TYPES OF SAGITTAL SKELETAL Malocclusion in a Sample of Syrian Orthodontic Patients with CBCT (A Retrospective Study) - ناصر رامي; فادي خليل (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The purpose of this study was to evaluate the relationship between the cranial base and various types of sagittal skeletal discrepancies using CBCT in a sample of adult Syrian patients. Methods and methods: This study was designed as a Retrospective Study on a sample of 45 patients selected from the archives of the Orthodontics Department at the Faculty of Dentistry - Tishreen University. They were distributed into three skeletal groups (Class I, II and III) based on ANB angle. The radial variables studied in this study were (NSBa, N-S, S-Ba, and N-Ba). Class I: ANB range of (2° to 4°) Class II: ANB angle more than 4° Class III: ANB angle less than 2°. Results: Cranial base angle and cranial base lengths did not show significant differences between the main classes of malocclusion studied. In addition, no statistically significant differences were seen between the lengths of the cranial base, cranial angle, and angle ANB within each class of malocclusion. Conclusions: Cranial base angle and lengths has no major role in developing malocclusion. In addition, no statistically significant differences were seen between the lengths of the cranial base, the cranial angle, and the ANB angle within each type of malocclusion.